A techno-economic and environmental assessment of residential rooftop solar - Battery systems in grid-connected households in Lagos, Nigeria. (2021) - Udeani, Chukwudi; Jaramillo, Paulina; Williams, Nathaniel J.
Abstract: We developed a techno-economic model to simulate the performance of residential solar-battery systems as a means of reducing the reliance on backup generators in grid connected households in Lagos, Nigeria. We compared the economic and environmental performance of solar-battery systems to the technology options in households that may currently rely on backup generators to supplement unreliable grid service. Our analysis shows that solar-battery systems are economically profitable for households who rely on their backup generators to ensure at least 8-h of reliable service daily. We also show that the solar-battery systems could offer a cost-effective alternative for households intending to increase the level of the electricity services they receive without greater demand from backup generators. Finally, installing the solar-battery system lowers annual air emissions from households by 15 %–87 %. The paper proposes that policymakers provide access to low interest loans to improve the economic attractiveness of solar-battery systems across all the reliability preference levels.